Prontidão para mudança em usuários de crack e cocaína que consomem tabaco e que estão em tratamento em uma comunidade terapêutica - Güths, Paula Beatriz (2013)
The prevalence of smoking among illicit drug users is significantly higher than the prevalence of smoking in the general population. It is known that in patients who use tobacco and cocaine, tobacco exposure may activate and increase crack cocaine administration. When treating a patient in parallel with comorbid dependencies you need to understand the differences and specificities of each substance, and realize their internship and their motivational readiness to change for each one separately. The goal of the empirical study was to determine, among patients who were in treatment for cocaine and crack use and were smokers, readiness to change for illicit substances and tobacco and its possible association. A methodology descriptive and correlational design, quantitative and cross. From a simple probability sample of 88 patients were admitted to a Therapeutic Farm in the metropolitan region of Porto Alegre. The instruments used to check the readiness to change for illicit substances and tobacco were the Algorithm, the Ruler of Readiness and URICA, using also a socio-economic questionnaire semi-structured questionnaire and the Fagerstrom for nicotine dependence. Regarding the results identified significant differences between the readiness for tobacco and illicit substances (p <0.001). According to the three instruments, individuals are more ready to change in relation to illicit substances than tobacco. While the prevalence of pre-contemplation is among tobacco users (79.5%), the highest prevalence of action and maintenance are among users of illicit substances (33% and 28.4%) for the URICA. In relation to the algorithm for the tobacco sample also prevailed in the stage of precontemplation (39.3%), whereas for illicit substances, the majority (75.3%) was found in the preparation. Thus concludes that tobacco users are less ready to change with regard to readiness to change in crack and cocaine. We also performed a systematic review, which was aimed to investigate the association of smoking on treatment of cocaine users and crack. Regarding the results, there was a direct association between following smoking during treatment for cocaine and worst results for the same treatment in the short and long term. From the systematic review concluded that consuming tobacco negatively affects the outcome of treatment for cocaine users. Thus it is suggested that treatments are offered concurrently and that health professionals also consider the readiness for change in motivational approaches related to tobacco consumption.